HUBUNGAN KEPEMIMPINAN GENERAL MANAGER DENGAN PERILAKU KERJA KARYAWAN DI HOTEL BUMIMINANG PADANG - Pasaribu, Sriandani; Chair, Ira Meirina; Kasmita, Kasmita (Journal of Home Economics and Tourism, 2015)
This study is aims to: 1) determine leadership of GM, 2) determine behavior employee, 3) analyze relationship between GM leadership with employee’s behavior at Hotel Bumiminang Padang. This research with correlational system. Population in this research amounted to 83 people. With samples 83 people with non-probability sampling technique, the sampling using saturated. Data were collected by questionnaire and analyzed by descriptive analysis or correlation. The results showed GM's leadership in a good category (78.31%). Behavior of employees in a good category (83.13%). Results of correlation test there is a significant connection between leadership of GM with working behavior with correlation value 0.261 and 0.017 significance and interpretation of weak values Keywords: Behavior, Performance, Work, Employee